Single walled carbon nanotube (SWNT) based electromagnetic interference (EMI) shielding - Zheng, Hanbin. (2009)
Indium Tin Oxide (ITO) has long been the material of choice in the manufacture of transparent conductive coatings for use in flat panel displays, organic light emitting diodes, solar cells and electronic devices. However, due to several factors, single walled carbon nanotubes (SWNT) are seen as potential replacements to ITO. This project focuses on the synthesis, purification, separation of SWNTs, and the subsequent production of thin SWNT films / coatings. The SWNT solutions used for the manufacture of the SWNT films are first tested using UV Spectroscopy and Photoluminescence Excitation (PLE) to determine the type and abundance of SWNT contained within. These solutions are then used for the manufacture of SWNT films via filtration and spray coating. The films were tested for their transmittance and shielding effect (SE). The results obtained showed that SWNT films produced via spray coating had higher transmittance and better SE than films formed by filtration. Furthermore, the experimental results proved that sulfuric acid doping of the films improved the transmittance and SE of the films by up to 500%. Enriched SWNT solutions, obtained via density gradient ultracentrifugation (DGU), were also tested to determine the abundance and type of SWNT contained within. The results showed that the enriched SWNT solutions contained a higher concentration of a particular type of SWNT based on their density (which is dependent on their chirality). This proves that it is possible to separate SWNT according to their different chirality.